A manipulative thermal challenge protocol for adult salmonids in remote field settings. Issue 1 (14th September 2020) - Donnelly, Daniel S; von Biela, Vanessa R; McCormick, Stephen D; Laske, Sarah M; Carey, Michael P; Waters, Shannon; Bowen, Lizabeth; Brown, Randy J; Larson, Sean; Zimmerman, Christian E
Abstract : A portable experimental system was developed for remote field settings, capable of holding large fish for several hours, while controlling for precise water temperatures. This system was used to conduct a thermal challenge experiment using adult Chinook salmon along the Yukon River in Alaska, USA. Abstract: Manipulative experiments provide stronger evidence for identifying cause-and-effect relationships than correlative studies, but protocols for implementing temperature manipulations are lacking for large species in remote settings. We developed an experimental protocol for holding adult Chinook salmon ( Oncorhynchus tshawytscha ) and exposing them to elevated temperature treatments. The goal of the experimental protocol was to validate heat stress biomarkers by increasing river water temperature from ambient (~14°C) to a treatment temperature of 18°C or 21°C and then maintain the treatment temperature over 4 hours within a range of ±1.0°C. Our protocol resulted in a mean rate of temperature rise of 3.71°C h-1 (SD = 1.31) to treatment temperatures and mean holding temperatures of 18.0°C (SD = 0.2) and 21.0°C (SD = 0.2) in the low- and high-heat treatments, respectively. Our work demonstrated that manipulative experiments with large, mobile study species can be successfully developed in remote locations to examine thermal stress.